Impact of carbon and nitrogen sources on pectinase production of post-harvest fungi - Rajmane, S D; Korekar, S L (Current Botany, 2012)
In the present investigation, emphasis has been given on to study the pectinase enzyme production of post-harvest fungi isolated from mango and papaya fruits, under the influence of carbon and nitrogen sources. It was found that, among carbon sources fructose and sucrose induced pectinase activity, while lactose, CMC and starch inhibited the pectinase activity of test fungi. Nitrate source like sodium nitrate, sodium nitrite and calcium nitrate were found to be stimulated the pectinase activity while, ammonium sources in the form of nitrate, phosphate and sulphate were proved inhibitory for pectinase production of all post-harvest fungi.